Green Construction in Malaysia: Integrating Regulation, Sustainability, and Innovation for a Resilient Future - Mohd Yusof, Ahmad Faizal; Yusnar, Cut; Illahi, Yuangga Rizky; Maharjan, Rabin; Widyasamratri, Hasti (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
Malaysia's construction industry has experienced steady growth since its independence, with the infrastructure sector projected to reach a market value of approximately USD 41.85 billion. This review article aims to evaluate the industry through the lens of environmental compliance, technological advancement, and sustainable development practices. Despite contributing to a 4.1% increase in Gross Domestic Product (GDP) over the past two decades, the industry continues to exert significant environmental pressure. To address these challenges, strict adherence to environmental regulations and standards is essential. One critical requirement is the development of an Environmental Management Plan (EMP) prior to project commencement. The EMP outlines procedures such as baseline environmental assessments, identification of potential adverse impacts, emergency response planning, stakeholder roles and responsibilities, staff training, and ongoing monitoring and enforcement. In parallel with regulatory compliance, the transition toward green construction practices is gaining momentum. This includes the use of sustainable materials such as recycled concrete and aerogels, and the integration of smart technologies like Building Information Modeling (BIM) and drone-based site monitoring. These innovations not only enhance construction efficiency and safety but also reduce the industry's ecological footprint. This paper explores the dynamic interplay between environmental responsibility, regulatory frameworks, and technological innovation, positioning green construction as a vital pathway for Malaysia’s sustainable development.